Entrepreneurial Leadership in Upstream Oil and Gas Industry - Kalu, Mona Ukpai (2015)
The study examined Entrepreneurial leadership in Upstream Oil and Gas industry and its ability to accelerate innovative energy technology development. The declining deliverability from existing reservoirs and ever increasing demand for energy to fuel growth in many parts of the world is driving oil and gas exploration into more difficult to access reservoirs like bituminous sands and shale gas. Accelerating new innovative technology development to access these new streams of profitable oil and gas resources necessitates a more opportunity recognition and exploitation focused leadership style which raises the question, does the Upstream Exploration and Production (E and P) industry possess such entrepreneurial leadership skills? In other to achieve the set objective, employee perception of entrepreneurial leadership was quantitatively examined by administering online questionnaire to E and P professionals in Malaysia. Based on the analysis of 90 valid responses the study found that the Malaysian E and P industry lack Entrepreneurial leadership with the goal of rapid opportunity recognition and exploitation. Furthermore, a significant relationship was found between Psychological empowerment and Entrepreneurial leadership supporting the first hypothesis H1. Also significant is the relationship between Entrepreneurial orientation and Entrepreneurial leadership. The non-linearity of these two relationships for the E and P industry is attributed to a lack of leadership focus on new opportunity exploration and exploitation. It therefore recommends among other things to increase industry strategic focus on rapid opportunity exploration and exploitation though leadership role modelling of entrepreneurial behaviors to encourage participation at all levels. Entrepreneurial orientation and culture will be developed through enabling policies and adequate resource provision to support new opportunity exploration.